DFT and molecular dynamics studies of astaxanthin-metal ions (Cu2+ and Zn2+) complex to prevent glycated human serum albumin from possible unfolding. Issue 3 (March 2021) - Wibowo, Syahputra; Widyarti, Sri; Sabarudin, Akhmad; Soeatmadji, Djoko Wahono; Sumitro, Sutiman Bambang
Abstract: Glycated human serum albumin (gHSA) undergoes conformational changes of proteins caused by free radicals. The glycation process results in a reduced ability of albumin as an endogenous scavenger in diabetes mellitus type 2 (T2DM) patients. Astaxanthin (ASX) has been shown to prevent gHSA from experiencing unfolding events and improve protein stability of gHSA and HSA through molecular dynamics. In this study, astaxanthin is complexed with transition metal ions such as copper (Cu 2+ ) and zinc (Zn 2+ ) in two modes (M) and (2M). Complexing astaxanthin with Cu 2+ and Zn 2+ is expected to increase astaxanthin's ability as an endogenous scavenger than in native form. This research aims to characterize the antiradical property of ASX, ASX-Cu 2+ and ASX-2Cu 2+, ASX-Zn 2+, and ASX-2Zn 2+ with density functional theory (DFT) and to compare the capability to prevent conformational changes on glycated albumin through molecular dynamics simulation. DFT as implemented in Gaussian 09W, was used for all calculations. Analysis of data using GaussView 6.0. LANL2D2Z basis set and B3LYP density functional used for frequency analysis and optimization. The AutoDock Vina implemented in PyRx 0.8 is used to and receptor-ligand interactions analysis with the DS 2016 Client. YASARA for molecular dynamic simulation with 15, 000 ps as running time. DFT analyzes such as energy gaps, HOMO, and LUMO patterns and electronic properties have shown that ASX-metal ions complex is better than ASX in native state as antioxidants. These results are also supported by the molecular dynamics simulation (RMSD backbone, RMSDr, RMSFr, and movie visualization), where the addition of ASX-metal ions complex on gHSA are better than ASX as a single compound in preventing gHSA from possible unfolding and maintaining protein molecule stability. Abstract : Astaxanthin, Density Functional Theory, Gaussian 09W, Molecular Dynamics Simulation, Transition Metal Ions.